Ultrafast dynamics of electrons and phonons in graphitic materials - Chatzakis, Ioannis (Kansas State University, 2009)
This work focuses on the ultrafast dynamics of electrons and phonons in graphitic materials. In particular, we experimentally investigated the factors which influence the transport properties of graphite and carbon nanotubes. In the first part of this dissertation, we used Time-resolved Two Photon photoemission (TR-TPP) spectroscopy to probe the dynamics of optically excited charge carriers above the Fermi energy of double-wall carbon nanotubes (DWNTs). In the second part of this study, time-resolved anti-Stokes Raman (ASR) spectroscopy is applied to investigating in real time the phonon-phonon interactions, and addressing the way the temperature affects the dynamics of single-wall carbon nanotubes (SWNTs) and graphite. With respect to the first part, we aim to deeply understand the dynamics of the charge carriers and electron-phonon interactions, in order to achieve an as complete as possible knowledge of DWNTs. We measured the energy transfer rate from the electronic system to the lattice, and we observed a strong non-linear increase with the temperature of the electrons. In addition, we determined the electron-phonon coupling parameter, and the mean-free path of the electrons. The TR-TPP technique enables us to measure the above quantities without any electrical contacts, with the advantage of reducing the errors introduced by the metallic electrodes. The second investigation uses time-resolved ASR spectroscopy to probe in real time the G-mode non-equilibrium phonon dynamics and the energy relaxation paths towards the lattice by variation of the temperature in SWNTs and graphite. The lifetime range of the optically excited phonons obtained is 1.23 ps to 0.70 ps in the lowest (cryogenic temperatures) and highest temperature limits, respectively. We have also observed an increase in the energy of the G-mode optical phonons in graphite with the transient temperature. The findings of this study are important since the non-equilibrium phonon population has been invoked to explain the negative differential conductance and current saturation in high biased transport phenomena.
Keywords: Temperature dependence of the anharmonic decay of optical phonons in graphite; Temperature dependence of the anharmonic decay of optical phonons in nanotubes; Zone center phonon dynamics in graphite; Zone center phonon dynamics in carbon nanotubes; Time resolved two photon photoemission spectroscopy in carbon nanotubes; Time resolved anti stokes Raman spectroscopy in carbon nanotubes; Physics, Condensed Matter (0611)